Bestimmung des zerebralen Blutflusses mittels des 81 Rb/81 mKr-Generatorsystems - Schroth, H.-J.; Bialy, J.; Hans, F.-J.; Oberhausen, E.; Peters, W.J.; Schmitt, M.; Warnke, R (Nuklearmedizin - NuclearMedicine, 1990)
A method is being developed which not only measures cerebral blood flow as a static quantity but also its changes with time. For that purpose a semiconductor device ascertains the proportion of intracerebral81 Rb and 81mKr activities. By opening the haemato-encephalic barrier in animal experiments a sufficient concentration of intracerebral81 Rb could be attained and the modified blood circulation after step-wise ligature of all brain arteries brought into relation to the corresponding Rb/Kr quotient. Over the range from undisturbed to completely interrupted cerebral blood flow this quotient varied up to 25% of its initial value.